The optical properties of the stratospheric aerosol layer perturbation of the Hunga Tonga–Hunga Ha'apai volcano eruption of 15 January 2022 - P. Sellitto; P. Sellitto; R. Belhadji; B. Legras; A. Podglajen; C. Duchamp (Atmospheric Chemistry and Physics, 2025)
The Hunga Tonga–Hunga Ha'apai volcano violently erupted on 15 January 2022 and produced the largest stratospheric aerosol layer perturbation of the last 30 years. In comparison to background conditions and other recent moderate stratospheric eruptions, one notable effect of the Hunga Tonga–Hunga Ha'apai eruption was the significant modification of the size distribution (SD) of the stratospheric aerosol layer, resulting in a larger mean particle size and a smaller SD spread for Hunga Tonga–Hunga Ha'apai. Starting from satellite-based SD retrievals and the assumption of pure sulfate aerosol layers, in this work, we calculate the optical properties of both background and Hunga Tonga–Hunga Ha'apai-perturbed stratospheric aerosol scenarios using a Mie code. We found that the intensive optical properties of the stratospheric aerosol layer (i.e. the single-scattering albedo (SSA), the asymmetry parameter, the aerosol extinction per unit mass, and the broad-band average ultraviolet–visible (UV–Vis) to mid-infrared (MIR) Ångström exponent (AE)) were not significantly perturbed by the Hunga Tonga–Hunga Ha'apai eruption with respect to background conditions. The calculated AE was found to be consistent with multi-instrument satellite observations of the same parameter. Thus, the basic impact of the Hunga Tonga–Hunga Ha'apai eruption on the optical properties of the stratospheric aerosol layer was an increase in the stratospheric aerosol extinction (or optical depth), without any modification of the shortwave (SW) and longwave (LW) relative absorption, angular scattering, and broad-band spectral trend of the extinction, with respect to background. This highlights a marked difference between the Hunga Tonga–Hunga Ha'apai perturbation of the stratospheric aerosol layer and perturbations from other larger stratospheric eruptions, such as Pinatubo 1991 and El Chichón 1982. With simplified radiative forcing estimations, we show that the Hunga Tonga–Hunga Ha'apai eruption produced an aerosol layer likely 1.5–10 times more effective in producing a net cooling of the climate system with respect to the Pinatubo and El Chichón eruptions due to more effective SW scattering. As intensive optical properties are seldom directly measured, e.g. from satellite, our calculations can support the estimation of radiative effects for the Hunga Tonga–Hunga Ha'apai eruption with climate or offline radiative models.